The effect of administrative control on the effectiveness of decisions in Omani government institutions - Al-Shezawi, Hatem Abdullah Muhammad (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to identify the impact of administrative control on the effectiveness of decisions in Omani government institutions, through a field study conducted in the Environment Authority of Oman. The researcher used the descriptive analytical method in conducting this study. Where the questionnaire was used to collect primary data, which consisted of all 31 managers in the Environment Authority of Oman, and after collecting the data, the SPSS statistical program was used to analyze the data. The study has reached several important results, the most prominent of which were: The presence of a statistically significant effect at the level of significance (α ≤ 0.05) between the administrative control in its dimensions (administrative reports - observations - the estimated budget - complaints) and the effectiveness of the decision-making process in its various stages (defining the problem, gathering information, identifying strategic alternatives, implementation and control) in the Environment Authority of Oman. In the light of the results of the study, the researcher recommends several recommendations, the most important of which are: Enhancing communication channels between the management of the Environment Authority of Oman and its employees, especially to discuss the various decisions taken by the department. Providing the senior management within the authority with periodic reports that clarify the strengths and weaknesses of the decisions issued by it, through a specialized committee.